On the Earthliness of Life in Yaakov Shabtai's Novels - Adaf, Shimon (MiKAN, 2014)
Yaakov Shabtai’s novels are often referred to as either metaphysical works or as a realistic depiction of Israeli life. Yet, the experience of transcendence of everyday life that the metaphysical view suggests stands in opposition to a strong impression of earthliness that the realistic depiction has to offer. The essay “On the Earthliness of Life” explores the deep nature and worldview of the two novels written by Shabtai from which these two seemingly exclusive readings stem.